Generations on the Line. Working Class Culture and Generational Conflict among Workers at an Italian Factory - Moro, Angelo (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
In their multiple attempts to understand the decline of the working class a number of sociologists have questioned changes in intergenerational relationships, analyzing transformations happened not only within the factory, but also outside it (in school, job market, family relations, labor activism). Inspired by this approach, particularly developed in French sociology, I conducted an ethnographic research among a group of workers employed at a automotive factory in Italy. This paper argues that, if transformations in the contexts of socialization have produced a generational gap within the working class, a conflict between “older” and “younger” workers is activated, in the context of the factory, by specific management policies. Nevertheless, the generational frame represents less a deterministic structure than a “constraining environment” that offers room for a partial composition of the generational conflict and an appropriation of the old working class culture by new generations.